GAMBARAN PERSONAL HYGIENE PENDERITA PENYAKIT SCABIES DI WILAYAH KERJA UPTD PUSKESMAS WANADADI 1 TAHUN 2021 - Bayu Suseno; Susi Muliayu (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Scabies is a skin infection caused by Sarcoftes scabiei, a type of small mite that lives in the patient's skin. Transmission can occur directly and indirectly. One of the effects of scabies disease is poor personal hygiene. The purpose of this study was to describe the personal hygiene of people with scabies in the working area of UPTD Health Center Wanadadi 1 in 2021. The method applied in this study is a descriptive method with a cross sectional approach. Data were obtained by conducting interviews and filling out questionnaires for patients. Data analysis was carried out descriptively and presented in tabular form. Based on the results of personal hygiene research on 31 respondents, it was found that bathing habits (77.4%) of scabies patients with good categories were the most common and for poor categories the most found in hair hygiene (54.8%) with poor categories. The conclusion from the results of the study that most of the results of the 31 respondents had quite good personal hygiene, but in hair hygiene there were still many that were not good. It is expected that more attention to personal hygiene and environmental cleanliness.